DEVELOPING WRITING SKILLS IN TEACHING UZBEK AS A FOREIGN LANGUAGE: THEORETICAL AND METHODOLOGICAL FOUNDATIONS (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the theoretical and methodological foundations for developing writing skills in the context of teaching Uzbek as a foreign language. Writing is considered a crucial component of foreign language acquisition, and the study highlights the main challenges faced by foreign learners. Modern teaching methods and global best practices for enhancing writing proficiency are analyzed, with a focus on their applicability to Uzbek language instruction. The research findings provide methodological recommendations and offer insights for future academic studies in the field.